KAJIAN EKSPERIMENTAL PENGARUH CAMPURAN ETANOL DAN PERTAMAX TERHADAP KONSUMSI BAHAN BAKAR MOTOR INJEKSI 125CC - Rauf, Wawan (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
Abstract: Experimental Study of the Effect of a Mixture of Ethanol and Pertamax on Fuel Consumption of a 125cc Injection Motorcycle. Currently the need for petroleum is quite high. This is because transportation and industry still rely on petroleum as the main fuel. Ethanol has similar properties to Pertamax fuel which can be applied to every vehicle, especially two-wheeled vehicles. The aim of this research is to find out how the addition of ethanol to Pertamax fuel affects the amount of fuel consumed by injection motorbikes. The mixture percentages that will be tested are E10+P90, E20+P80, and E30+P70 respectively, and then the consumption results are compared with tests using pure Pertamax (E0+P100). The test results show that the use of Ethanol-Pertamax mixed fuel can be reduced when the percentage of the ethanol mixture is below 50%. Where the lowest fuel consumption is the E30+P70 mixture at 16.4% compared to pure Pertamax consumption.